PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI PEGAWAI PERUSAHAAN PADA MITRA PT.PLN (PERSERO) ULP KOTA BIMA - Nurseha Nurseha; muhammad Yusuf (Jurnal Bina Manajemen, 2021)
This study aims to determine the effect of work motivation and job satisfaction on organizational commitment of company employees at partners PT.PLN (Persero) ULP Kota Bima. This research was conducted at Partners PT.PLN (Persero) ULP Kota Bima. This research was conducted using associative research. The population used in this research is 46 employees of the contract at partners of PT. PLN (Persero) Ulp. Bima City are 46 employees. With a research sample of 34 permanent employees, with the sampling technique using purposive sampling technique. Data collection techniques used, 1, observation, 2 documentation, 3, questionnaire 4, literature study. The data analysis technique used is, validity test, reliability test, classic assumption test, normality test, multicolinearity test, heteroscedasticity test, correlation coefficient test, determination coefficient test, multiple regression analysis test, hypothesis test (t test and F test). The results of this study indicate that Work Motivation and Job Satisfaction simultaneously influence the Company's Employee Organizational Commitment at Partners PT PLN (Persero) ULP Kota Bima.